Gleason score and lethal prostate cancer: does 3 + 4 = 4 + 3? - FINN, STEPHEN (My University, 2009)
PURPOSE Gleason grading is an important predictor of prostate cancer (PCa) outcomes. Studies using surrogate PCa end points suggest outcomes for Gleason score (GS) 7 cancers vary according to the predominance of pattern 4. These studies have influenced clinical practice, but it is unclear if rates of PCa mortality differ for 3 + 4 and 4 + 3 tumors. Using PCa mortality as the primary end point, we compared outcomes in Gleason 3 + 4 and 4 + 3 cancers, and the predictive ability of GS from a standardized review versus original scoring. PATIENTS AND METHODS Three study pathologists conducted a blinded standardized review of 693 prostatectomy and 119 biopsy specimens to assign primary and secondary Gleason patterns. Tumor specimens were from PCa patients diagnosed between 1984 and 2004 from the Physicians' Health Study and Health Professionals Follow-Up Study. Lethal PCa (n = 53) was defined as development of bony metastases or PCa death. Hazard ratios (HR) were estimated according to original GS and standardized GS. We compared the discrimination of standardized and original grading with C-statistics from models of 10-year survival. Results For prostatectomy specimens, 4 + 3 cancers were associated with a three-fold increase in lethal PCa compared with 3 + 4 cancers (95% CI, 1.1 to 8.6). The discrimination of models of standardized scores from prostatectomy (C-statistic, 0.86) and biopsy (C-statistic, 0.85) were improved compared to models of original scores (prostatectomy C-statistic, 0.82; biopsy C-statistic, 0.72). CONCLUSION Ignoring the predominance of Gleason pattern 4 in GS 7 cancers may conceal important prognostic information. A standardized review of GS can improve prediction of PCa survival.
PUBLISHED
Keywords: Oncology; Prostate Cancer; Gleason grading